KEADAAN SOSIAL EKONOMI NELAYAN SOMA GIOP DI DESA LELEOTO KECAMATAN TOBELO SELATAN KABUPATEN HALMAHERA UTARA PROVINSI MALUKU UTARA - Atihuta, Velsia Marle D.; Aling, Djuwitha R.R.; Lumenta, Vonne (Universitas Sam Ratulangi, 2014)
Abstract The study was conducted aim to analyze the socio-economic condition of soma giop fishermen whoâ€™s Living in Leleoto fishing community, South Tobelo District, North Halmahera Regency, North Moluccas Province. Data was collected based in census method that is gathering data from all 5 owners of soma giop fishing gear. The result of study indicated that averagely the ages of fishermen are 31 years old with 35 to 40 years experiences working on this kind of livelihood. The study also found still there are mutual works among community members however, there are also bad custom to drink alcoholic beverages. The reset of study also found the maximum catch are 7,403.33 kg while minimum catch is 33.33 kg. The distribution system of catch is 50% for owners and 50% for vessel crews. Keywords: socio-economic, soma giop, fishermen, livelihood, distribution system of catch Â Abstrak Penelitian ini mengkaji tentang keadaan sosial ekonomi nelayan pemilik alat tangkap soma giop di desa leleoto, Kecamatan Tobelo Selatan, Kabupaten Halmahera Utara, Provinsi Maluku Utara. Metode pengumpulan data dilakukan dengan cara sensus terhadap obyek yang menjadi tujuan penelitian, yaitu semua nelayan pemilik alat tangkap soma giop yang berjumlah 5 orang. Rata-rata umur nelayan 31 tahun, dan nelayan soma giop yang memiliki pengalaman kerja, yaitu 35 tahun sampai 40 tahun. Berdasarkan hasil penelitian masih terdapat kegiatan gotong royong dan masih adanya kebiasaan nelayan, yaitu minum minuman beralkohol. Hasil tangkapan tertinggi 7.403,33 kg dan terendah 33,33 kg. Sistem bagi hasil 50% untuk nelayan pemilik dan 50% untuk nelayan pekerja. Kata Kunci: sosial ekonomi, soma giop, nelayan, rumah tangga, system bagi hasil